School-based language screening among primary school children using telepractice: A feasibility study from India. - Raman, Nitya; Nagarajan, Roopa; Venkatesh, Lakshmi; Monica, D. Saleth; Ramkumar, Vidya; Krumm, Mark (International Journal of Speech-Language Pathology, 2019)
Purpose: This study explored the feasibility of conducting school-based language screening using telepractice to expand its scope for providing speech-language pathology services in India. Method: Thirty-two primary school children underwent language screenings through in-person and telemethods. Screening through telemethod was conducted by a Speech-Language Pathologist (SLP) using digitised picture stimuli presented through videoconferencing and remote computing with assistance of a facilitator at school site. Technology and child-related factors influencing screening were documented using an inventory. Result: Language outcomes through in-person and telemethods revealed no significant differences in both receptive and expressive domains, suggesting absence of bias due to testing method used. Use of multiple internet options at both sites helped overcome technical challenges related to connectivity during screening through telemethod. The trained facilitator played a crucial role in overcoming child related factors such as poor speech intelligibility, poor audibility of voice, motivation, interaction with SLP and need for frequent breaks. Conclusion: Feasibility of conducting school-based language screening using multiple internet options and help of a facilitator at school demonstrates promise for delivery of services by SLP in resource constrained contexts such as India.